2017
DOI: 10.1002/2016gl072008
|View full text |Cite
|
Sign up to set email alerts
|

Rough versus smooth topography along oceanic hotspot tracks: Observations and scaling analysis

Abstract: Some hotspot tracks are topographically smooth and broad (Nazca, Carnegie/Cocos/Galápagos, Walvis, Iceland), while others are rough and discontinuous (Easter/Sala y Gomez, Tristan‐Gough, Louisville, St. Helena, Hawaiian‐Emperor). Smooth topography occurs when the lithospheric age at emplacement is young, favoring intrusive magmatism, whereas rough topography is due to isolated volcanic edifices constructed on older/thicker lithosphere. The main controls on the balance of intrusive versus extrusive magmatism ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 53 publications
0
5
0
1
Order By: Relevance
“…This anomalous density contrast causes strong buoyancy forces and subsequently the formation of the broad swell (shallow seafloor) topography (McNutt & Bonneville, 2000; see detailed discussion of the swell topography in the next subsection). For the case of the NR, the swell surface is up to 1.5 km shallower than the surrounding seafloor (Figures 1 and 2) and is characterized by a smooth morphology compared to other hot spot tracks formed by hot spot plumes located far from active spreading centers such as the Juan Fernandez Ridge and the Hawaiian volcanic chain (e.g., Orellana-Rovirosa & Richards, 2017). According to these authors, the smooth swell topography occurs when the hot spot plume is overlying by an oceanic lithosphere young, and therefore weak, thin, and hot, allowing voluminous melt penetration and crustal intrusion.…”
Section: Oceanic Crust and Mantle Beneath The Nrmentioning
confidence: 98%
See 2 more Smart Citations
“…This anomalous density contrast causes strong buoyancy forces and subsequently the formation of the broad swell (shallow seafloor) topography (McNutt & Bonneville, 2000; see detailed discussion of the swell topography in the next subsection). For the case of the NR, the swell surface is up to 1.5 km shallower than the surrounding seafloor (Figures 1 and 2) and is characterized by a smooth morphology compared to other hot spot tracks formed by hot spot plumes located far from active spreading centers such as the Juan Fernandez Ridge and the Hawaiian volcanic chain (e.g., Orellana-Rovirosa & Richards, 2017). According to these authors, the smooth swell topography occurs when the hot spot plume is overlying by an oceanic lithosphere young, and therefore weak, thin, and hot, allowing voluminous melt penetration and crustal intrusion.…”
Section: Oceanic Crust and Mantle Beneath The Nrmentioning
confidence: 98%
“…For example, seamounts formed near a spreading center on weak oceanic plate (on-ridge seamounts like the Cocos and Nazca ridges) are locally more compensated and more buoyant (Watts et al, 2010), and thus, an important coupling at the subduction interface is expected. In addition, these oceanic ridges are characterized by a smooth and broad morphology (Orellana-Rovirosa & Richards, 2017) and more basal subduction erosion beneath the upper plate rather than frontal subduction erosion at the front of the upper plate is hypothesized (Contreras-Reyes & Carrizo, 2011). In contrast, oceanic ridges formed far from oceanic spreading center (off-ridge seamounts like the Juan Fernandez and Louisville ridges) are more regionally compensated, and therefore less buoyant (Watts et al, 2010), and host a rough and narrow morphology (Orellana-Rovirosa & Richards, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geodynamic considerations show that hotspot tracks are characterized by time‐dependent topography, with elevated topography above and in the vicinity of the underlying plume conduit (Davies, ; Ribe & Christensen, ), responding to the fluid dynamics of ponding and buoyancy of highly viscous flows (Sleep, ). Aside from this, geophysical studies have demonstrated the regular time dependence of ocean basin depth with plate age (Johnson & Carlson, ), as well as the associated effects upon volcanism (Orellana‐Rovirosa & Richards, ). Below we review how mechanical and thermodynamic considerations regarding plate tectonics, mantle plume dynamics, crustal dynamics, and volcanism can account for paleo‐elevations with respect to the current topography/bathymetry of the region.…”
Section: Introductionmentioning
confidence: 99%
“…При объяснении морфологического облика того или иного «трас сера» основной упор делается на кинематические особенности и скорость дрейфа океанической плиты в сочетании с магматичес кой активностью «горячей точки». По особенностям взаимодей ствия этих процессов «трассеры» могут быть прерывистые (к ним, например, относят Гавайский хребет), или сплошные, типа хребта Наска [22]. Структурные особенности ВИХ, как «трассера горячей точки», рас сматриваются в работах последних лет [17, 24, 25, 26 и др.…”
Section: Introductionunclassified